Skin disorders prevalent among orphanage children in Puducherry - Kanagaraj, Preethi; Kaliyaperumal, Damayandhi; Paquirissamy, Oudeacoumar (International Journal of Research in Dermatology, 2021)
Background: Around 20 million children, about 4% of the total population of India, higher than the population of Delhi, are abandoned and most of them dwell in orphanages. Methods: There are only few studies were carried out to analyse the spectrum of skin diseases in orphanage children and there is a paucity of data from orphanages in Puducherry. Hence this study was carried out to analyse the spectrum of skin disorders in orphanage children, in and around Puducherry. In this cross sectional study, three orphanages in and around Puducherry was chosen. Two dermatologists carried out the examination, including the skin, hair, nails and oral cavity of all the residents for a period of six months. Diagnoses were made clinically and recorded, treatment recommendations were offered. Results: The data analysis was carried out using Graphpad Prism, a p<0.05 was considered significant. A total of 216 children were enrolled in this study, of which 203 (93.98%) were found to have skin diseases. Infectious dermatoses were observed in 148 (68.52%) children whereas non-infectious dermatosis was evident in 83 (32.43%). Among the infectious dermatoses infestation was the most common (37.50%), followed by fungal in 48 (22.22%), bacterial 12 (5.56%) and viral in 7 (3.20%). Acquired disorders such as acne, eczema and xerosis and pigmentary, papulosquamous and other miscellaneous dermatoses constituted the non-infectious group dermatoses. Conclusions: Skin disorders in orphanage children are ought to be more common due to overcrowding, lack of personal hygiene etc, which is evident from higher incidence of contagious infectious dermatoses. Hence improving the standard of living, counseling and education to the care takers, and the children and good nutrition will help to bring down the skin diseases in orphanages.